Membrane Topology of the Streptomyces lividans Type I Signal Peptidases - Geukens, Nick (American Society for Microbiology, 2001)
Most bacterial membranes contain one or two type I signal peptidases (SPases) for the removal of signal peptides from export proteins. For Streptomyces lividans, four different type I SPases (denoted SipW, SipX, SipY, and SipZ) were previously described. In this communication, we report the experimental determination of the membrane topology of these SPases. A protease protection assay of SPase tendamistat fusions confirmed the presence of the N- as well as the C-terminal transmembrane anchor for SipY. SipX and SipZ have a predicted topology similar to that of SipY. These three S. lividans SPases are currently the only known prokaryotic-type type I SPases of gram-positive bacteria with a C-terminal transmembrane anchor, thereby establishing a new subclass of type I SPases. In contrast, S. lividans SipW contains only the N-terminal transmembrane segment, similar to most type I SPases of gram-positive bacteria. Functional analysis showed that the C-terminal transmembrane anchor of SipY is important to enhance the processing activity, both in vitro as well as in vivo. Moreover, for the S. lividans SPases, a relation seems to exist between the presence or absence of the C-terminal anchor and the relative contributions to the total SPase processing activity in the cell. SipY and SipZ, two SPases with a C-terminal anchor, were shown to be of major importance to the cell. Accordingly, for SipW, missing the C-terminal anchor, a minor role in preprotein processing was found.